The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14148812
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scenario Simulation of Ecosystem Service Values in the Guanzhong Plain Urban Agglomeration, China

Abstract: Rapid urbanization and human activities enhanced threats to the degradation of various ecosystem services in modern urban agglomerations. This study explored the response of ecosystem service values (ESVs) to land use changes and the trade-offs among various ESVs in urban agglomerations under different future development scenarios. The patch-general land use simulation (PLUS) model and ESV calculation method were used to simulate the ESVs of Guanzhong Plain Urban Agglomeration under the Business As Usual scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 83 publications
2
11
0
Order By: Relevance
“…Spatial auto-correlation is an important indicator to test the correlated significance of the attribute value of an index with the attribute value of its adjacent space [78]. The Global Moran's index reflects the correlation of attribute values of adjacent spatial units of the whole area.…”
Section: Global Moran's Indexmentioning
confidence: 99%
“…Spatial auto-correlation is an important indicator to test the correlated significance of the attribute value of an index with the attribute value of its adjacent space [78]. The Global Moran's index reflects the correlation of attribute values of adjacent spatial units of the whole area.…”
Section: Global Moran's Indexmentioning
confidence: 99%
“…The implementation of the national food security strategy and targeted poverty alleviation strategy proposed at the 2013 Central Rural Work Conference has greatly increased humans' income and improved farmland protection. In addition, Yang Ke et al found that although the annual average PM2.5 concentration in the Guanzhong Plain urban agglomeration showed an overall downward trend from 2015 to 2019, it still exceeded China's air quality Level II (35 µg/m 3 ) [43]. Therefore, human well-being recovered from 2015 to 2018 but did not reach its initial level.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the patch-level land use simulation model (PLUS) of the integrated development type was used to simulate urban land expansion. Compared with other urban land expansion simulation models, the PLUS model integrates a CA based on multi-type random patch seeds (CARS), the land expansion rule mining framework (LEAS), and a multi-type stochastic seed mechanism, which obtain more accurate patch-level land use type simulation results, especially for natural land use types, such as woodland and grassland [16,35]. The spatiotemporal dynamic evolution characteristics of land use, ESVs, and the coupling relationship between them were quantified.…”
Section: Data Source and Processingmentioning
confidence: 99%
“…In recent years, scholars have achieved a series of productive results in the study of ES and LULC [15]. At the research scale, the relationship between land use and ES in watersheds, coastal wetlands, water-bearing lands, and urbanized areas has been explored [16,17]. In terms of research Land 2022, 11,1934 3 of 23 content, ES is used as a basis for constructing ecological resistance surfaces, ecological safety patterns, and ecological health patterns and for predicting urban land expansion processes.…”
Section: Introductionmentioning
confidence: 99%